EFEKTIVITAS ANGGARAN DALAM MENJALANKAN PROGRAM/KEGIATAN DI BALAI KONSERVASI BOROBUDUR TAHUN 2017 & 2018 - Ulfa Nurul Hidayah; Yustirania Septiani (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2021)
A budget is a design that is structured in the form of numbers and is expressed in terms of monetary units that cover all of the company's activities within a certain time span. Budgeting stage is a stage that is very important because a budget that is not effective and does not lead to performance can result in failure of programs or activities that have been prepared. The purpose of this research is to analyze the level of budget effectiveness at the 2017-2018 Borobudur Conservation Center in realizing the budget per activity-output. The analytical method used in this study is a quantitative descriptive method with effectiveness measurement calculations. The results showed that the realization of the budget per activity-output of the Borobudur Conservation Center in 2017 and 2018 on average as a whole was carried out effectively and the programmed activities had been realized in accordance with the planned objectives. Keywords: budget, effectiveness, output_activities